Pelatihan Penggunaan Paint Untuk Melatih Motorik Siswa Anak Sekolah Dasar - Paryono, Tukino; Novalia, Elfina; Yoga Astario, Bayu; Hananto, Agustia (VIDHEAS: Jurnal Nasional Abdimas Multidisiplin, 2024)
This training program aims to assist elementary school students in developing their fine motor skills by utilizing Paint software. Fine motor skills, which involve coordinating small muscles like the hands and fingers, are essential for children's growth and development. In this activity, Paint is used as a tool to enhance both students' creativity and their motor abilities. Students engage in activities such as drawing, coloring, and pattern-making, which improve hand-eye coordination and establish fundamental artistic skills. The outcomes of this training reveal significant improvements in students' fine motor skills as well as their proficiency in using technology for creative purposes.